Obstructive sleep apnea - A review - Sharma, S. M.; Gohil, Saurabh (Journal of Health and Allied Sciences NU, 2015)
Sleep related problems affect large group of people of all ages around world. One of the most common disorders is Obstructive Sleep Apnea (OSA) characterized by repetitive, complete or partial collapse of upper airway during sleep. Due to complexity of disease and associated medical conditions, a broad spectrum of clinicians play important roles in treatment of OSA. Evaluation of OSA is best performed using a multidisciplinary team approach.This article aims to reviewthe exhaustive current literature for relevant information regarding terminology, pathophysiology, prevalenceand treatment including conservative and surgical.
Keywords: Obstructive sleep apnea; Epworth sleepiness scale; Continuous Positive Airway Pressure (CPAP) Therapy; Polysomnography; Osteotomy; Palatal implants